A Kind of Robot Structure Design and Kinematics Analysis - Yankai Hu; Hui Fu (Jixie chuandong)
Humanoid robots are an important part of the field of robotics，and their characteristics analysis involves disciplines such as machinery，electronics，and materials. Since humanoid robots can imitate human behaviors and actions and can better serve humans，it has become a current research hotspot most humanoid robots are equipped with a large number of intelligent software and hardware，but the body design still has defects，especially the waist structure design of humanoid robots，which is not innovative and restricts the overall function. Based on this，a kind of humanoid robot waist structure is designed，it has a certain degree of innovation. Firstly，its pose is calculated by using the spin theory. Secondly，by using the Adams and Matlab，the simulation fitting is carried out. Finally，it is verified by experiments to prove the rationality and feasibility of the structure design，it lays the foundation for robot dynamics analysis.